1939
DOI: 10.1021/ac50130a003
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Detemination of Traces of Metals

Abstract: In most inorganic tests using organic materials the pH must be somewhat controlled. The molybdenum test using tincture of cochineal which is sensitive to 0.02 gamma of molybdenum oxide must be carried out at a pH between 5.7 and 6.2.It is hoped that fluorescence will add to the specific test for the elements. Such a case is illustrated in the Pontachrome Blue Black R (2S) test for aluminum, which is sensitive to 0.2 gamma of aluminum-ion concentration and to a dilution of one part in ten million. It serves to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

1946
1946
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…To do a proof-of-concept study, dithizone was taken as an example in this study, which had been reported showing different color responses to diverse metal ions 32 33 . Given requirements of the practical application, ten common heavy metal ions (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…To do a proof-of-concept study, dithizone was taken as an example in this study, which had been reported showing different color responses to diverse metal ions 32 33 . Given requirements of the practical application, ten common heavy metal ions (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…(20.30 =*= 0.82) X 103, respectively. Coefficients for lead, zinc, silver, and mercury(Il) dithizonates are QUANTITATIVE spectrochemical micromethods have been expanded considerably in recent years through the use of dithizone {18, 15, 16). Although a large amount of work has been done to develop new procedures in the application of dithizone and to improve existing ones, in general the development has been along empirical lines.…”
Section: Application and Accuracymentioning
confidence: 99%
“…of copper and up to 5°(Lg.of mercury per litre of sea water. Mercury in the absence of copper may be readily estimated in these concentrations by the use of dithizone, and the tentative curves of Wichmann (1939) suggest that it is completely extracted even at pH 2'0. However, according to these curves copper is also partially extracted at this acidity.…”
Section: Introductionmentioning
confidence: 99%